COVID-19 vaccination perceptions and intentions of maternity care consumers and providers in Australia - Bradfield, Zoe; Wynter, K.; Hauck, Yvonne; Sweet, L.; Wilson, A.N.; Szabo, R.A.; Vasilevski, V.; Kuliukas, Lesley; Homer, C.S.E. (PUBLIC LIBRARY SCIENCE, 2021)
Introduction: Vaccination against COVID-19 is a key global public health strategy. Health professionals including midwives and doctors support and influence vaccination uptake by childbearing women. There is currently no evidence regarding the COVID-19 vaccination perceptions and intentions of those who receive or provide maternity care in Australia. The aim of this study was to address this gap in knowledge and explore the perceptions and intentions regarding COVID-19 vaccination from consumers and providers of maternity care in Australia.